Effect of Xanthan Gum and pH on Pasting Properties and Freeze-Thaw Stability of Tapioca Starch - Suwapat Srijunthongsiri; Rungnaphar Pongsawatmanit (Agriculture and Natural Resources, 2006)
Effect of xanthan gum on the viscosity and thermal stability of tapioca starch (TS) at different mixing ratios of TS and xanthan gum under different pH values was investigated using a Rapid Visco-Analyzer (RVA) and repeated freeze-thaw treatment. At a total polysaccharide concentration of 5% (w/w) tapioca starch (TS) and TS/xanthan gum mixtures, the RVA peak and final viscosity values increased with xanthan gum concentration. Final viscosity of gelatinized TS alone under pH 3 exhibited the lowest value compared with those of TS at pH 5 and 7 but the extent of difference between those of pH 3 and pH 5 or 7 was lower with increasing gum content. Freeze-thaw stability of TS pastes containing xanthan gum exhibited lower water separation (<10%) compared with that of TS pastes alone (>10%) after 3 cycles of repeated freeze-thaw treatment. This study shows that the substitution of a part of tapioca starch with xanthan gum can improve pasting properties and the freeze–thaw stability of tapioca starch under acidic systems which could be applied to food industry.